Multi-objective Optimization of Dimensional Parameter for 4-PRPaR Parallel Mechanism - Jian Yi; Bing He; Linxian Che; Jie Li (Jixie chuandong)
Taking a 4-PRPaR parallel mechanism with three translational and one rotational as the research object， the evolutionary multi-objective algorithm is applied to solve the dimensional synthesis problem of mechanism. The degree of freedom of mechanism is analyzed by means of constraint screw theory， and the analytical expression of the inverse position solution of mechanism is given. These works can be foundations for the mechanism performance analysis. The evaluation indices for motion and force transmission performance of mechanism are established， and the definition of regular effective transmission workspace （RETW） and its average transmission indices are presented. A multi-objective optimization model is constructed to formulate the design problem of dimensional parameters on the maximizing radius of RETW and average transmission indices， and the fast and elitist multi-objective genetic algorithm combined with differential evolution algorithm is used to solve this problem. A real case of multi-objective optimization for dimensional parameters is given， and the result shows that the model and algorithm are feasible and effective. The research results can provide a theoretical basis for the practical application and the development of physical prototype.